Impact of ion exchange resins comparing to oenological additives on wine quality - Borges, Rita (2019)
Tartaric acid is easily ionized, leading to the formation of precipitates like potassium hydrogen tartrate (KHT) and calcium tartrate (CaT CaT). Although, not harmful to consumer health, these precipitates leads to a decrease in the commercial commercial value of the wine. To prevent the occurrence of these precipitations precipitations several treatments can be used.